Pengaruh Jumlah Daun yang disisakan pada Pemangkasan Cabang Lateral terhadap Hasil Polong Muda Tanaman Kacang Panjang (Vigna sinensis L.) - SRINING, KETUT; RAKA, I GUSTI NGURAH; ASTININGSIH, A.A. MADE; WIJAYA, I KETUT ARSA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
The Effect of Lateral Branch Trimming Against Results and Quality of Long Bean Seeds (Vigna sinensis L.) This study aims to determine the effect of the number of leaves that are left on the lateral branch roasting on the results of young pods of long bean plants. This tudy uses a randomized block design (RBD). Treatment of the number of leaves left on lateral branch pruning includes: total lateral pruning, leaving 2 leaves, leaving 4 eaves, leaving 6 leaves and leaving 8 leaves on lateral branch pruning. This research was repeated 5 times, so as many as 25 experimental units were obtained. Variables observed included: main stem length, total number of leaves per plant, total leaf area per plant, fresh weight and oven dry weight of plant parts above ground, number of harvest pods per plant, fresh pod weight per plant, weight of oven dried pods per plant and the weight of fresh pods per hectare. The results showed that more leaves were left on the lateral branch pruning causing the number of leaves, leaf area, weight of the plant part above the ground, and oven dry weight of the plant part on he ground to increase. Total lateral pruning pruning treatment resulted in the number of crop harvest pods, fresh pod weight, and oven pod dry weight with the highest average value. The total lateral pruning treatment resulted in the highest per hectare fresh pod weight of 25.59 tons.